Full immersion simulation: validation of a distributed simulation environment for technical and non‐technical skills training in Urology. (7th March 2015) - Brewin, James; Tang, Jessica; Dasgupta, Prokar; Khan, Muhammad S.; Ahmed, Kamran; Bello, Fernando; Kneebone, Roger; Jaye, Peter
<x xml:space="preserve">Abstract</x> Objective To evaluate the face, content and construct validity of the distributed simulation (DS) environment for technical and non‐technical skills training in endourology. To evaluate the educational impact of DS for urology training. Subjects and Methods DS offers a portable, low‐cost simulated operating room environment that can be set up in any open space. A prospective mixed methods design using established validation methodology was conducted in this simulated environment with 10 experienced and 10 trainee urologists. All participants performed a simulated prostate resection in the DS environment. Outcome measures included surveys to evaluate the DS, as well as comparative analyses of experienced and trainee urologist's performance using real‐time and 'blinded' video analysis and validated performance metrics. Non‐parametric statistical methods were used to compare differences between groups. Results The DS environment demonstrated face, content and construct validity for both non‐technical and technical skills. Kirkpatrick level 1 evidence for the educational impact of the DS environment was shown. Further studies are needed to evaluate the effect of simulated operating room training on real operating room performance. Conclusions This study has shown the validity of the DS environment for non‐technical, as well as technical skills training. DS‐based simulation appears to be a valuable addition to traditional classroom‐based simulation training.